1961
DOI: 10.1136/oem.18.1.41
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Aspergillus Spores in the Atmosphere of a Modern Mill

Abstract: A study has been made of the atmospheric pollution by aspergillus spores of a large animal provender mill in which various grains are unloaded, stored, and processed, and a comparison has been made with the degree of pollution of the urban atmosphere in the neighbourhood. The catch-rate of the spores in the normal working atmosphere of the mill has been found to be 30 times higher than that obtained in the urban atmosphere, and for this reason the health record of a group of operatives has been considered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In one of the men who died, only chronic bronchiolitis and bronchiectasis was found, but no evidence of aspergillosis. Stallybrass' (1961) study of atmospheric pollution by aspergillus spores in a large animal-provender mill, in which various grains were unloaded, stored, and processed, tends to confirm this view. The catch rate of spores in the normal working atmosphere of the mill was 30 times higher than appeared in the urban atmosphere, and of all the grains handled, maize was the most highly contaminated.…”
Section: Discussionmentioning
confidence: 93%
“…In one of the men who died, only chronic bronchiolitis and bronchiectasis was found, but no evidence of aspergillosis. Stallybrass' (1961) study of atmospheric pollution by aspergillus spores in a large animal-provender mill, in which various grains were unloaded, stored, and processed, tends to confirm this view. The catch rate of spores in the normal working atmosphere of the mill was 30 times higher than appeared in the urban atmosphere, and of all the grains handled, maize was the most highly contaminated.…”
Section: Discussionmentioning
confidence: 93%
“…The average concentration is 10• spores/m3 (Gregory 1961). In the air of a closed place we registered a concentration of over 106 spores/m3 up to 1 Q9 spores/m~ specially in environments where leaves and moldy hay is mov,ed, or in food industries (Barkai·Golan, 1961;Stallybrass, 1961;Gregory, 1963;Kotimaa, 1977;Lacey, 1962Lacey, , 1971Lacey, , 1973Sreeramulu, 1958;Darke et al_,, 1976, Gregory et aL., 1963.…”
Section: Introductionmentioning
confidence: 81%
“…Stallybrass (1961) and Dunner et al (1958) studied men working with flour and grain and found no evidence of pulmonary aspergillosis, though atmospheric pollution with Aspergillus spores was very high.…”
Section: Epidemiologymentioning
confidence: 99%